Does democracy protect? The United Kingdom, the United States, and Covid‐19. (7th December 2021) - Keen, David
Abstract : The Covid‐19 crises in the United Kingdom and the United States show how democracies may struggle to confront disasters that are increasingly impinging on the Global North. This paper highlights the extent to which disasters are now 'coming home' to Western democracies and it looks at some of the principal reasons why democracy has not been especially protective, at least in the case of the UK and the US. These include: reconceptualising disaster as a good thing (via 'herd immunity'); the influence of neoliberalism; and the limitations in the circulation of information. A key pandemic‐related danger is the conclusion that democracy itself is discredited. Disasters, though, call for a reinvigoration of democracy, not a knee‐jerk invocation of autocratic 'emergency' rule. A fundamental problem in the UK and US is that these countries were not democratic enough. The paper underlines the risk of a move towards a disaster‐producing system that is self‐reinforcing rather than self‐correcting.